Proof-of-Minimum Privacy Leak Consensus Strategy in Blockchain - Yogi, Manas Kumar; Mundru, Yamuna; Prasad Pennada, Siva Satya (E-COMMERCE FOR FUTURE & TRENDS, 2022)
In this study, we propose a novel consensus algorithm to preserve the security and privacy of a transaction. We propose a Proof-of-Minimum Privacy Leak consensus strategy. This means that the competing nodes which participate in the competition to mine the next block should give a proof of minimum privacy leak during its transaction. Only this proof will give highest votes to that node, and it will be elected as the leader. The minimum privacy leak of a node participating in a Blockchain depends on various factors intrinsic to the Blockchain application. For example, if the application is related to healthcare, it will be related to the sensitive data of a patient, if it is a banking application, it will be related to monetary aspects of the account holder, etc. For our study, we apply the proposed approach to a smart voting system where Blockchain is deployed. Here, the participants’ details during voting are private data and there are provisions to reduce the voter privacy so that the participants of the smart voting system gain trust in the system rather than doubting that their privacy will be preserved or not. Our proposed mechanism performs better than recent popular consensus algorithms as shown in the experimental result. The results are displayed in terms of improved scalability, reliability and degree of increased trust.